Ichnology of the brackish water intervals of the Puesto el Moro Formation, Upper Cretaceous, Austral Basin, Argentina - Varela, Augusto Nicolás (2013)
The Puesto El Moro Formation (Upper Cretaceous) was originally considered as a continental succession overlying the Piedra Clavada Formation. This unit is exposed in the region of Lake San Martin, near the homonymous Outpost belonging to the Estancia La Lila. The Puesto El Moro Formation is coeval with the Mata Amarilla Formation; both formations are of great interest because they mark the onset of the foreland stage of the Austral Basin. A detailed sedimentological logging at the type locality allows the identification of three main intervals. The lower interval corresponds to a littoral paleoenvironment, and the middle and upper intervals were developed in continental (fluvial) paleoenvironment. The lower littoral interval is composed of an alternation of commonly bioturbated medium-grained sandstone, with greyish flaser-bedded heterolithic deposits, locally exhibiting trace fossils. The ichnofauna is dominated by Thalassinoides isp., accompanied by Ophiomorpha nodosa, Palaeophycus isp. and Sinusichnus sinuosus. This ichnoassociation corresponds to an impoverished Cruziana Ichnofacies developed in a marginal shallow marine palaeoenvironment with salinity stress and / or oxygen depletion. Most of these ichnotaxa are produced by callianassid crustaceans that used the galleries for different purposes, including dwelling (domichnia) and bacteria cultivation (agrichnia). Similar examples, which could be used as analogues for paleoenvironmental characterization, can be found in the Pliocene marginal marine deposits of France and Spain (the type locality of the ichnogenus Sinusichnus), in deltaic deposits of the Oligocene-Miocene of Venezuela, and in the Cretaceous of Antarctica.